Method for manufacturing mask blank, reflective mask, and semiconductor device

The use of a tantalum-molybdenum-nitrogen thin film in mask blanks and reflective masks addresses the slow etching rates of TaMo alloys, enhancing productivity and pattern accuracy in EUV lithography by optimizing etching rates and selectivity, and maintaining effective EUV light reflection.

KR103041716B1Active Publication Date: 2026-11-03HOYA CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020237042219
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-10
Filing Date
2022-05-31
Publication Date
2026-11-03
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

Existing reflective masks in EUV lithography face issues with slow etching rates and insufficient etching selectivity ratios due to the use of alloys like TaMo, leading to reduced productivity and pattern accuracy.

Method used

A mask blank and reflective mask configuration using a thin film composed of tantalum, molybdenum, and nitrogen, with specific atomic ratios and properties to enhance etching rates and selectivity, and a multilayer reflective film for improved EUV light reflection.

Benefits of technology

The solution provides a mask blank with a fast etching rate and improved etching selectivity, resulting in higher productivity and pattern accuracy, while maintaining optimal refractive indices and decay coefficients for EUV light reflection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112023136799565-PCT00001_ABST
    Figure 112023136799565-PCT00001_ABST
Patent Text Reader

Abstract

A mask blank is provided having a thin film with a sufficiently fast etching speed. The mask blank is provided with a multilayer reflective film (2) and a pattern forming thin film (4) in this order on the main surface of a substrate, wherein the thin film (4) contains tantalum, molybdenum, and nitrogen, and the ratio of the nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum of the thin film (4) is 0.15 or higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a mask blank for an exposure mask used in the manufacture of semiconductor devices, a reflective mask which is a reflective exposure mask using the mask blank, and a method for manufacturing a semiconductor device using the reflective mask. Background Technology

[0002] As a manufacturing technology for semiconductor devices, EUV lithography using Extreme Ultra Violet (EUV) with a wavelength of around 13.5 nm is being developed. In EUV lithography, reflective masks are used because there are few materials that are transparent to EUV light. For reflective masks, the exposure light, EUV light, is incident from an oblique angle. Because of this, a unique problem called the shadowing effect occurs. The shadowing effect refers to a phenomenon in which shadows are formed on an absorber pattern having a three-dimensional structure when the exposure light (EUV light) is incident from an oblique angle, causing the dimensions or position of the transferred pattern to change. To suppress this shadowing effect, it is necessary to thin the absorber film constituting the absorber pattern in the mask blank, which serves as the base plate for the reflective mask.

[0003] As one method for thinning an absorber film, there is a method of using a reflective mask as a reflective phase shift mask (reflective halftone phase shift mask) by configuring the absorber film using a low refractive index material. As a technical description of the method, the following patent documents 1 and 2 exemplify the use of an alloy such as TaMo as a material constituting the halftone film.

[0004] In addition, regarding the technology for reflective masks, the following patent document 3 describes mask blanks in which the absorber film has an absorber layer composed of an absorber of EUV light as the lower layer and a low-reflection layer composed of an absorber of inspection light used for inspecting mask patterns as the upper layer. That is, patent document 3 describes that the exposure light absorber of the lower layer in the absorber layer may be composed of at least one material selected from chromium, manganese, cobalt, copper, zinc, gallium, germanium, molybdenum, palladium, silver, cadmium, tin, antimony, tellurium, iodine, hafnium, tantalum, tungsten, titanium, gold, alloys containing these elements, and materials containing these elements or alloys containing these elements and nitrogen and / or oxygen. Prior art literature

[0005] Japanese Patent Publication No. 2006-228766, Japanese Patent Publication No. 2018-146945, Japanese Patent Publication No. 2004-6798 The problem to be solved

[0006] Here, the absorber pattern of the reflective mask is obtained by patterning the absorber film by etching. Therefore, if the etching rate of the absorber film is fast, it is expected that the productivity of the reflective mask and the etching selectivity ratio with respect to the etching mask or underlying layer will improve. However, the alloys such as TaMo mentioned above have a slow etching rate, and the etching selectivity ratio with respect to the etching mask or underlying layer is insufficient.

[0007] Accordingly, the present invention aims to provide a mask blank having a thin film with a sufficiently fast etching rate.

[0008] The present invention also aims to provide a reflective mask formed using this mask blank.

[0009] The present invention also aims to provide a method for manufacturing a semiconductor device using this reflective mask. means of solving the problem

[0010] To solve the above problem, the present invention has the following configuration.

[0011] (Composition 1)

[0012] A mask blank having a multilayer reflective film and a thin film for pattern formation in this order on the main surface of a substrate, and

[0013] The above thin film comprises tantalum, molybdenum, and nitrogen, and

[0014] A mask blank in which the ratio of nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the above thin film is 0.15 or higher.

[0015] (Composition 2)

[0016] A mask blank described in Composition 1, wherein the ratio of nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 1.0 or less.

[0017] (Composition 3)

[0018] A mask blank described in Composition 1 or 2, wherein the ratio of the molybdenum content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 0.5 or less.

[0019] (Composition 4)

[0020] A mask blank described in any one of claims 1 to 3, wherein the total content of tantalum, molybdenum, and nitrogen in the thin film is 90 atomic percent or more.

[0021] (Composition 5)

[0022] A mask blank described in any one of claims 1 to 4, wherein the refractive index n of the thin film at the wavelength of extreme ultraviolet light is 0.955 or less.

[0023] (Composition 6)

[0024] A mask blank described in any one of claims 1 to 5, wherein the decay coefficient k of the thin film at the wavelength of extreme ultraviolet light is 0.02 or greater.

[0025] (Composition 7)

[0026] A reflective mask having a multilayer reflective film and a thin film having a transfer pattern formed thereon in this order on the main surface of a substrate, and

[0027] The above thin film comprises tantalum, molybdenum, and nitrogen, and

[0028] A reflective mask in which the ratio of nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the above thin film is 0.15 or higher.

[0029] (Composition 8)

[0030] A reflective mask described in Composition 7, wherein the ratio of nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 1.0 or less.

[0031] (Composition 9)

[0032] A reflective mask described in Composition 7 or 8, wherein the ratio of the molybdenum content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 0.5 or less.

[0033] (Composition 10)

[0034] A reflective mask described in any one of claims 7 to 9, wherein the total content of tantalum, molybdenum, and nitrogen in the thin film is 90 atomic percent or more.

[0035] (Composition 11)

[0036] A reflective mask described in any one of claims 7 to 10, wherein the refractive index n of the above thin film at the wavelength of EUV is 0.955 or less.

[0037] (Composition 12)

[0038] A reflective mask described in any one of claims 7 to 11, wherein the decay coefficient k of the thin film at the wavelength of extreme ultraviolet rays is 0.02 or greater.

[0039] (Composition 13)

[0040] A method for manufacturing a semiconductor device comprising using a reflective mask described in any one of claims 7 to 12 and a process of photolithographically transferring a transfer pattern onto a resist film on a semiconductor substrate. Effects of the invention

[0041] According to the present invention, a mask blank having a thin film having a sufficiently fast etching rate, a reflective mask formed using the mask blank, and a method for manufacturing a semiconductor device using the reflective mask can be provided. Brief explanation of the drawing

[0042] FIG. 1 is a cross-sectional view showing the configuration of a mask blank according to an embodiment of the present invention. FIG. 2 is a cross-sectional view showing the configuration of a reflective mask according to an embodiment of the present invention. Figure 3 is a graph showing the nitrogen content ratio [N] / [Ta+Mo] and the etching rate ratio in a TaMoN thin film. Figure 4 is a graph showing the relationship between the molybdenum content ratio [Mo] / [Ta+Mo], refractive index [n], and decay coefficient [k] in a TaMoN thin film. Figure 5 is a manufacturing process diagram showing the method for manufacturing a reflective mask of the present invention. Figure 6 is a diagram showing the thin film composition and physical properties of an embodiment of the present invention. Specific details for implementing the invention

[0043] ≪Mask Blanks and Reflective Masks≫

[0044] FIG. 1 is a cross-sectional view showing the configuration of a mask blank (100) according to an embodiment of the present invention. The mask blank (100) shown in this figure is a plate of a reflective mask for EUV lithography that uses extreme ultraviolet light (EUV: Extreme Ultra Violet, hereinafter referred to as EUV light) as exposure light.

[0045] In addition, FIG. 2 is a cross-sectional view showing the configuration of a reflective mask (200) according to an embodiment of the present invention, and is manufactured by processing the mask blank (100) shown in FIG. 1. Hereinafter, the configuration of the mask blank (100) and the reflective mask (200) according to an embodiment will be explained using FIG. 1 and FIG. 2.

[0046] The mask blank (100) illustrated in FIG. 1 has a substrate (1) and a multilayer reflective film (2), a protective film (3), and a thin film (4) stacked sequentially from the substrate (1) side on the main surface (1a) on one side of the substrate (1). The thin film (4) is a film on which a transfer pattern is formed by processing. Additionally, the mask blank (100) may be configured to have an etching mask film (5) provided on the thin film (4) as needed. This mask blank (100) has a conductive film (10) on the main surface (hereinafter referred to as the back side (1b)) on the other side of the substrate (1).

[0047] The reflective mask (200) shown in FIG. 2 is formed by patterning the thin film (4) in the mask blank (100) shown in FIG. 1 as a transfer pattern (4a). Below, details of each part constituting the mask blank (100) and the reflective mask (200) will be explained based on FIG. 1 and FIG. 2.

[0048] <Board (1)>

[0049] In order to prevent deformation of the transfer pattern (4a) due to heat generation during exposure (EUV exposure) using EUV light with a reflective mask (200), the substrate (1) preferably uses a material having a low thermal expansion coefficient within the range of 0±5 ppb / ℃. Examples of materials having a low thermal expansion coefficient within this range include SiO2-TiO2 glass, multi-component glass ceramics, etc. Additionally, the transfer pattern (4a) is a pattern formed by processing the thin film (4) as described above.

[0050] The main surface (1a) of the substrate (1) is surface-processed to have high flatness in order to obtain pattern transfer precision and positional precision in EUV exposure using a reflective mask (200). In the case of EUV exposure, in the 132 mm × 132 mm area of ​​the main surface (1a) of the substrate (1), it is preferable that the flatness be 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.03 μm or less.

[0051] In addition, the back surface (1b) of the substrate (1) is a surface that is chucked by an electrostatic chuck method when a reflective mask (200) is set in an exposure device, and in an area of ​​132 mm × 132 mm, it is preferable that the flatness is 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.03 μm or less. In addition, the back surface (1b) of the mask blank (100) in an area of ​​142 mm × 142 mm is preferably 1 μm or less, more preferably 0.5 μm or less, and particularly preferably 0.3 μm or less.

[0052] In addition, the surface smoothness of the substrate (1) is also a very important factor. The surface roughness of the main surface (1a) of the substrate (1) is preferably 0.1 nm or less as the root mean square roughness [Sq] calculated within a square area with sides of 1 μm. In addition, the surface smoothness can be measured using an atomic force microscope.

[0053] In addition, the substrate (1) is preferably to have high rigidity in order to suppress deformation caused by film stress of the film formed on the main surface (1a) and the back surface (1b). In particular, the substrate (1) is preferably to have a high Young's modulus of 65 GPa or higher.

[0054] <Multilayer reflective film (2)>

[0055] The multilayer reflective film (2) is formed on the main surface (1a) and reflects EUV light, which is exposure light, with a high reflectivity. This multilayer reflective film (2) is a reflective mask (200) formed using this mask blank (100) that provides the function of reflecting EUV light, and is a multilayer film in which each layer, composed of elements with different refractive indices, is periodically stacked.

[0056] Generally, a multilayer film in which a thin film of a light element or its compound, which is a high refractive index material (high refractive index layer), and a thin film of a heavy element or its compound, which is a low refractive index material (low refractive index layer), are alternately stacked for about 40 to 60 cycles is used as a multilayer reflective film (2). The multilayer film may be stacked in multiple cycles, with the stacking structure of the high refractive index layer and the low refractive index layer stacked in this order from the substrate (1) side forming one cycle of the high refractive index layer / low refractive index layer stacking structure. In addition, the multilayer film may be stacked in multiple cycles, with the stacking structure of the low refractive index layer and the high refractive index layer stacked in this order from the substrate (1) side forming one cycle of the low refractive index layer / high refractive index layer stacking structure. In addition, the outermost layer of the multilayer reflective film (2), that is, the surface layer opposite to the substrate (1) of the multilayer reflective film (2), is preferably a high refractive index layer. In the multilayer film described above, when a stacking structure of a high refractive index layer and a low refractive index layer stacked in this order from the substrate (1) is stacked in multiple cycles with one cycle, the top layer becomes a low refractive index layer. In this case, if the low refractive index layer forms the outermost surface of the multilayer reflective film (2), it oxidizes easily, and the reflectivity of the reflective mask (200) decreases. Therefore, it is preferable to further form a high refractive index layer on the top layer of the low refractive index layer to form a multilayer reflective film (2). On the other hand, in the multilayer film described above, when a stacking structure of a low refractive index layer and a high refractive index layer stacked in this order from the substrate (1) side is stacked in multiple cycles with one cycle, the top layer becomes a high refractive index layer, so it may be left as is.

[0057] In the present embodiment, a layer containing silicon (Si) is employed as the high refractive index layer. As a material containing Si, in addition to Si alone, a Si compound containing boron (B), carbon (C), nitrogen (N), and oxygen (O) in Si can be used. By using a layer containing Si as the high refractive index layer, a reflective mask (200) for EUV lithography with excellent reflectivity of EUV light is obtained. In addition, in the present embodiment, a glass substrate is preferably used as the substrate (1). Si also has excellent adhesion to the glass substrate. In addition, as the low refractive index layer, a metal alone selected from molybdenum (Mo), ruthenium (Ru), rhodium (Rh), and platinum (Pt), or an alloy thereof, is used. For example, as a multilayer reflective film (2) for EUV light with a wavelength of 13 nm to 14 nm, a Mo / Si periodic multilayer film is preferably used in which Mo films and Si films are alternately stacked for about 40 to 60 periods. In addition, the high refractive index layer, which is the uppermost layer of the multilayer reflective film (2), may be formed of silicon (Si).

[0058] The reflectance of the multilayer reflective film (2) alone is typically 65% ​​or more, and the upper limit is typically 73%. The film thickness and period of each constituent layer of the multilayer reflective film (2) can be appropriately selected based on the exposure wavelength and are selected to satisfy the law of Bragg reflection. In the multilayer reflective film (2), there are multiple high-refractive-index layers and low-refractive-index layers, but the film thicknesses of the high-refractive-index layers and the low-refractive-index layers do not have to be the same. In addition, the film thickness of the outermost Si layer of the multilayer reflective film (2) can be adjusted within a range that does not reduce the reflectance. The film thickness of the outermost Si layer (high-refractive-index layer) can be in the range of 3 nm to 10 nm.

[0059] The method of forming a multilayer reflective film (2) is known in the art. For example, it can be formed by depositing each layer of the multilayer reflective film (2) by an ion beam sputtering method. In the case of the Mo / Si periodic multilayer film described above, for example, by an ion beam sputtering method, a Si film with a thickness of about 4.2 nm is first deposited on the substrate (1) using a Si target. Then, a Mo film with a thickness of about 2.8 nm is deposited using a Mo target. The multilayer reflective film (2) is formed by stacking 40 to 60 cycles with this Si film / Mo film as one cycle (the outermost layer is made of a Si layer). In addition, for example, if the multilayer reflective film (2) is made with 60 cycles, the number of process steps increases compared to 40 cycles, but the reflectivity for EUV light can be increased. In addition, when forming the multilayer reflective film (2), it is preferable to form the multilayer reflective film (2) by supplying krypton (Kr) ion particles from an ion source and performing ion beam sputtering.

[0060] <Protective shield (3)>

[0061] The protective film (3) is a film provided to protect the multilayer reflective film (2) from etching and cleaning when manufacturing a reflective mask (200) for EUV lithography by processing this mask blank (100). The protective film (3) is provided on the multilayer reflective film (2) in contact with the multilayer reflective film (2) or through another film. In addition, the protective film (3) also serves to protect the multilayer reflective film (2) when correcting black defects of the transfer pattern (4a) using an electron beam (EB) in the reflective mask (200).

[0062] Here, FIGS. 1 and 2 show a case where the protective film (3) is a single layer, but the protective film (3) may be a stacked structure of two or more layers. The protective film (3) is formed of a material that is resistant to the etchant and cleaning solution used when patterning the thin film (4). By forming the protective film (3) on the multilayer reflective film (2), damage to the surface of the multilayer reflective film (2) can be suppressed when manufacturing a reflective mask (200) using a substrate (1) having the multilayer reflective film (2) and the protective film (3). As a result, the reflectance characteristics of the multilayer reflective film (2) with respect to EUV light are improved.

[0063] Below, the case where the protective film (3) is a single layer is explained as an example. Also, when the protective film (3) has a stacked structure, the properties of the material of the uppermost layer of the protective film (3) (the layer in contact with the thin film (4)) become important in relation to the thin film (4).

[0064] In the mask blank (100) of the present embodiment, as the material of the protective film (3), a material that is resistant to the etching gas used for dry etching to pattern the thin film (4) formed on the protective film (3) can be selected.

[0065] The protective film (3) preferably contains ruthenium (Ru). The material of the protective film (3) may be a single Ru metal, or a Ru alloy containing at least one metal selected from titanium (Ti), niobium (Nb), molybdenum (Mo), zirconium (Zr), yttrium (Y), rhodium (Rh), boron (B), lanthanum (La), cobalt (Co) and rhenium (Re) in addition to ruthenium (Ru), and it may also contain nitrogen.

[0066] Meanwhile, the protective film (3) may be made of a silicon-based material selected from silicon (Si), a material containing silicon (Si) and oxygen (O), a material containing silicon (Si) and nitrogen (N), a material containing silicon (Si), oxygen (O) and nitrogen (N), etc.

[0067] In EUV lithography, there are few materials that are transparent to the EUV light used as the exposure light. For this reason, it is technically difficult to place a dust-proof mask (EUV pellicle) to prevent foreign matter from adhering to the formation surface of the transfer pattern (4a) on the reflective mask (200). For this reason, the operation of pellicles without using a dust-proof mask has become the mainstream. Furthermore, in EUV lithography, exposure contamination occurs, such as carbon film deposition or oxide film growth on the reflective mask (200) due to EUV exposure. Therefore, during the stage where the reflective mask (200) is used in the manufacture of a semiconductor device, it is necessary to frequently clean the mask to remove foreign matter or contamination. For this reason, the reflective mask (200) requires a mask cleaning resistance that is significantly different from that of a conventional photolithography transmission mask, and the reflective mask (200) can have a protective film (3) to increase its cleaning resistance to the cleaning solution.

[0068] The film thickness of the protective film (3) is not particularly limited as long as it can perform the function of protecting the multilayer reflective film (2). In terms of the reflectance of EUV light, the film thickness of the protective film (3) is preferably 1.0 nm or more and 8.0 nm or less, more preferably 1.5 nm or more and 6.0 nm or less.

[0069] As a method for forming the protective film (3), any known film forming method may be adopted without particular limitation. Specific examples include various sputtering methods, such as DC sputtering, RF sputtering, and ion beam sputtering, as well as atomic layer deposition (ALD).

[0070] <Thin film (4) and transfer pattern (4a)>

[0071] The thin film (4) is a film used as an absorbing film that absorbs EUV light, and serves as a film for forming a transfer pattern (4a) of a reflective mask (200) constructed using this mask blank (100). The transfer pattern (4a) is formed by patterning this thin film (4). In this embodiment, this thin film (4) is a TaMoN thin film containing tantalum (Ta), molybdenum (Mo), and nitrogen (N).

[0072] -Nitrogen content ratio[N] / [Ta+Mo]-

[0073] In this thin film (4), the ratio of the nitrogen (N) content [atomic %] to the total content [atomic %] of tantalum (Ta) and molybdenum (Mo) (nitrogen content ratio [N] / [Ta+Mo]) is 0.15 or higher.

[0074] Here, FIG. 3 is a graph showing the nitrogen content ratio [N] / [Ta+Mo] and the etching rate ratio in a TaMoN thin film. The etching rate ratio is the value when the etching rate of a tantalum (Ta)-molybdenum (Mo) alloy (Ta:Mo=7:3) that does not contain nitrogen (N) is set to 1. The tantalum (Ta)-molybdenum (Mo) alloy is an alloy having a refractive index suitable for use as a thin film for a phase shift mask.

[0075] In addition, the etching is a dry etching using chlorine gas (Cl2) as an etching gas, which is widely used in the manufacture of a reflective mask (200), and a dry etching using carbon tetrafluoride (CF4) as an etching gas. Also, the detailed composition of the thin film shown in FIG. 3 will be explained in a later example.

[0076] As shown in the graph of FIG. 3, a TaMoN thin film with a nitrogen content ratio [N] / [Ta+Mo] of 0.15 or higher has an etching rate ratio of 1.5 or higher in dry etching using chlorine gas (Cl2) as an etching gas. Furthermore, this etching rate ratio increases with increasing nitrogen content ratio [N] / [Ta+Mo]. Thus, by making the nitrogen content ratio [N] / [Ta+Mo] ≥ 0.15, it can be seen that the etching rate of the thin film (4) in dry etching using chlorine gas (Cl2) as an etching gas is 1.5 times or higher than the etching rate of the tantalum (Ta)-molybdenum (Mo) alloy.

[0077] In addition, as shown in the graph of FIG. 3, for a TaMoN thin film with a nitrogen content ratio [N] / [Ta+Mo] of 0.3 or higher, the etching rate ratio in dry etching using chlorine gas (Cl2) as an etching gas is 2 or higher. On the other hand, in the case of a thin film (TaN thin film) composed of tantalum (Ta) and nitrogen (N), as the nitrogen content ratio [N] / [Ta] increases, the etching rate ratio in dry etching using chlorine gas (Cl2) as an etching gas tends to decrease. That is, the relationship between the nitrogen content ratio and the etching rate ratio in dry etching using chlorine gas (Cl2) as an etching gas is significantly different between the case where nitrogen (N) is added to a tantalum (Ta)-based material that does not contain molybdenum (Mo) and the case where nitrogen (N) is added to a material containing tantalum (Ta) and molybdenum (Mo). In addition, the upper limit of the nitrogen content ratio [N] / [Ta+Mo] is set to ≤ 1.0 in order to keep the surface roughness of the thin film (4) small.

[0078] -Molybdenum content ratio[Mo] / [Ta+Mo]-

[0079] In this thin film (4), the ratio of the molybdenum (Mo) content [atomic %] to the total content [atomic %] of tantalum (Ta) and molybdenum (Mo) (molybdenum content ratio [Mo] / [Ta+Mo]) is preferably 0.5 or less.

[0080] FIG. 4 is a graph showing the relationship between the molybdenum content ratio [Mo] / [Ta+Mo], refractive index, and decay coefficient in a TaMoN thin film. The refractive index [n] and decay coefficient [k] are the refractive index [n] and decay coefficient [k] for the EUV wavelength. In addition, the detailed composition of the thin film shown in FIG. 4 will be explained in a later example.

[0081] As shown in the graph of FIG. 4, it can be seen that the TaMoN thin film with a molybdenum content ratio [Mo] / [Ta+Mo] of 0.5 or less maintains a decay coefficient [k] of 0.02 or more for the wavelength of EUV light. Meanwhile, as shown in the graph of FIG. 4, it can be seen that by including molybdenum in the thin film (4), the refractive index [n] for the wavelength of EUV light is maintained at 0.955 or less. In addition, it can be seen that by making the [Mo] / [Ta+Mo] of the TaMoN film 0.15 or more, the refractive index [n] for the wavelength of EUV light can be made 0.95 or less.

[0082] A TaMoN thin film having such a decay coefficient [k] and refractive index [n] can have its film thickness set to a thinner range. Therefore, when the reflective mask (200) is a phase shift mask, the transfer pattern (4a), which is a phase shift pattern, is thinned out, thereby suppressing the occurrence of a shadowing effect of the reflective mask (200).

[0083] -Overall Composition-

[0084] The thin film (4) described above preferably has a total content of tantalum (Ta), molybdenum (Mo), and nitrogen (N) of 90 atomic percent or more, more preferably 95 atomic percent or more, and even more preferably 100 atomic percent. In addition, if the thin film (4) contains materials other than tantalum (Ta), molybdenum (Mo), and nitrogen (N), such materials may be contained in the thin film (4). Other materials are, for example, boron (B), carbon (C), oxygen (O), and hydrogen (H).

[0085] As described in the following examples, it was found that the thin film (4) with the composition as described above has low surface roughness and film stress, and also has sufficient resistance to cleaning and contrast with ultraviolet and visible light.

[0086] For example, the thin film (4) has a thickness of about 50 nm, and the surface roughness [Sq] (root mean square roughness) is less than 0.3 nm. This root mean square roughness [Sq] is a value measured by using an atomic force microscope (AFM) on a thin film formed on a test substrate, with a square area with sides of 1 μm as the measurement area. In addition, the root mean square roughness [Sq] is a parameter for evaluating surface roughness specified in ISO 25178, and is a parameter that extends the line-direction root mean square roughness [Rq], which represents the two-dimensional surface characteristics previously specified in ISO 4287 and JIS B0601, to three dimensions (surface). A thin film (4) with such low surface roughness has amorphous crystallinity, and can reduce edge roughness when a pattern is formed on the thin film (4) by etching.

[0087] In addition, the film stress of the thin film (4) is such that the amount of deformation of the test substrate caused by forming this thin film (4) is 150 nm or less. The amount of deformation of the test substrate is expressed as the difference between the maximum height and the minimum height in the inner region of a rectangle with a side length of 142 mm, based on the center of the test substrate of the difference shape, by calculating the difference shape between the surface shape of the thin film (4) and the surface shape of the test substrate before forming the thin film (4). In addition, the test substrate is made of SiO2-TiO2 glass similar to the substrate (1) of the mask blank (100), and is of size 6025 (approx. 152 mm × 152 mm × 6.35 mm) with the main surfaces on both sides polished. The transfer pattern (4a) of the reflective mask (200) obtained by patterning the thin film (4) with low film stress in this way becomes a pattern with good formation position precision.

[0088] As a method for forming the thin film (4), any known film formation method may be adopted without particular limitation. Specific examples include various sputtering methods, such as DC sputtering, RF sputtering, and ion beam sputtering, as well as Atomic Layer Deposition (ALD). For example, when forming the thin film (4) by DC sputtering, a mixed target of tantalum (Ta) and molybdenum (Mo) is used, and the film is formed by a sputtering method using nitrogen gas (N2) as the sputtering gas. At this time, a thin film (4) satisfying the composition range described above is obtained by forming the film by adjusting the ratio of tantalum (Ta) and molybdenum (Mo) in the target, the flow rate of the sputtering gas, and the pressure of the sputtering gas. In addition, a thin film (4) may be formed by so-called co-sputtering, in which a tantalum (Ta) target and a molybdenum (Mo) target are installed in a film-forming chamber and voltage is applied to both targets simultaneously.

[0089] Here, when the thin film (4) is used as a phase shift film, the thickness of the thin film (4) is adjusted to have a reflectivity as follows. That is, when the transfer pattern (4a) of the reflective mask (200) is a phase shift pattern, this thin film (4) is configured as a phase shift film. Such a thin film (4) absorbs EUV light and reflects a portion of the EUV light at a level that does not adversely affect the pattern transfer. In addition, in the part where the transfer pattern (4a) is formed in the reflective mask (200), the protective film (3) is exposed at the opening where the thin film (4) is removed. Because of this, the EUV light irradiated on the reflective mask (200) is reflected to the surface of the thin film (4) and to the multilayer reflective film (2) through the protective film (3) exposed from the thin film (4).

[0090] In addition, when the transfer pattern (4a) is a phase shift pattern, the thin film (4) is set in material and film thickness such that the phase of the reflected EUV light at the surface of the thin film (4) and the phase of the reflected EUV light at the aperture where the thin film (4) is removed have a desired phase difference. This phase difference is approximately 130 to 230 degrees, and the reflected light with an inverted phase difference of around 180 degrees or around 220 degrees interferes with each other at the pattern edge, thereby improving the image contrast of the projected optical image. As the image contrast improves, the resolution increases, and various margins related to exposure, such as exposure amount margin and focus margin, are widened.

[0091] In order to obtain such a phase shift effect, the relative reflectance of EUV light on the surface of the thin film (4) is preferably 2% to 40%, more preferably 6% to 35%, even more preferably 15% to 35%, and particularly preferably 15% to 25%, although this varies depending on the pattern or exposure conditions. Here, the relative reflectance of the transfer pattern (4a) is the reflectance of EUV light reflected from the thin film (4) when the reflectance of EUV light reflected from the part without the thin film (4) is set to 100%.

[0092] Depending on the pattern or exposure conditions, in order to obtain a phase shift effect, the absolute reflectance of the thin film (4) (or the transfer pattern (4a) that becomes the phase shift pattern) to EUV light is preferably 1% to 30%, and more preferably 2% to 25%. The film thickness of the thin film (4) is set so that such absolute reflectance is obtained.

[0093] The film thickness of the thin film (4) is preferably less than 100 nm, and preferably 90 nm or less. In addition, the film thickness of the thin film (4) is preferably 15 nm or more, and more preferably 20 nm or more. The thin film (4) as described above can also be used as an absorber film for a binary mask by adjusting the film thickness. In addition, one or more other thin films may be formed above or below the thin film (4), and a phase shift film or an absorber film for a binary mask may be configured with a stacked structure of the thin film (4) and one or more other thin films. In this case, the ratio of the thin film (4) to the total film thickness of the phase shift film or absorber film is preferably 0.5 or more.

[0094] <Etching mask (5)>

[0095] The etching mask film (5) is a layer provided on the thin film (4) in the mask blank (100) or in contact with the surface of the thin film (4), and is a film that becomes a mask pattern when patterning the thin film (4). This etching mask film (5) may be removed at the stage where the reflective mask (200) is completed.

[0096] As a material for such an etching mask film (5), a material is used in which the etching selectivity ratio of the thin film (4) to the etching mask film (5) is sufficiently high. The etching selectivity ratio of the thin film (4) to the etching mask film (5) is preferably 1.5 or higher, and more preferably 3 or higher.

[0097] The thin film (4) in this embodiment is a TaMoN thin film containing tantalum (Ta)-molybdenum (Mo)-nitrogen (N), and has a nitrogen content ratio [N] / [Ta+Mo] of 0.15 or higher, and is a film with a high etching rate for dry etching using chlorine gas (Cl2) as the etching gas. For this reason, as the material for the etching mask film (5), it is preferable to use a material that has a low etching rate for dry etching using chlorine gas (Cl2) as the etching gas. As such a material, a material containing chromium (Cr) can be exemplified. Specific examples of a material containing chromium (Cr) include, for instance, a material containing chromium and one or more elements selected from nitrogen, oxygen, carbon, and boron. Specific examples of such a material include, for instance, CrN, CrON, CrCN, CrCON, CrBN, CrBON, CrBCN, and CrBOCN. An etching mask film (5) formed from a material containing chromium can be patterned by dry etching using a mixed gas of chlorine gas (Cl2) and oxygen gas (O2). When removing the etching mask film (5), the damage to the thin film (4) can be reduced by dry etching. These materials may contain metals other than chromium within the range where the effects of the present invention are obtained. The method of forming such an etching mask film (5) can be formed using a chromium (Cr) target, for example, by a magnetron sputtering method or an ion beam sputtering method.

[0098] In addition, when the pattern of the etching mask film (5) remains at the stage where the reflective mask (200) is completed and forms part of the phase shift pattern or part of the absorber pattern, the etching mask film (5) may be formed from a material containing silicon and oxygen or a material containing tantalum and oxygen.

[0099] The thickness of the etching mask film (5) is preferably 2 nm or more from the perspective of obtaining the function of an etching mask that forms a transfer pattern on a thin film (4) with high precision. In addition, the thickness of the etching mask film (5) is preferably 15 nm or less, and more preferably 10 nm or less, from the perspective of making the thickness of the resist film formed on the upper part of the etching mask film (5) thin when manufacturing a reflective mask (200) by processing the mask blank (100).

[0100] <Challenge (10)>

[0101] The conductive film (10) is a film for installing a reflective mask (200) to an exposure device by an electrostatic chuck method. The electrical characteristics (sheet resistance) required for such an electrostatic chuck conductive film (10) are typically 100Ω / □ (Ω / Square) or less. The method of forming the conductive film (10) can be, for example, by magnetron sputtering or ion beam sputtering, using a target of a metal or alloy such as chromium (Cr) and tantalum (Ta).

[0102] The chromium (Cr)-containing material of the conductive film (10) is preferably a Cr compound containing Cr and also containing at least one selected from boron (B), nitrogen (N), oxygen (O) and carbon (C).

[0103] As a material containing tantalum (Ta) for the conductive film (10), it is also preferable to use Ta (tantalum), an alloy containing Ta, or a Ta compound containing at least one of boron, nitrogen, oxygen, and carbon in any one of these.

[0104] The thickness of the conductive film (10) is not specifically limited as long as it satisfies the function as an electrostatic chuck. The thickness of the conductive film (10) is typically 10 nm to 200 nm. In addition, this conductive film (10) also serves to adjust the stress on the back side (1b) of the mask blank (100). That is, the thickness of the conductive film (10) is adjusted to balance the stress from various films formed on the main surface (1a) side so that a flat mask blank (100) and a reflective mask (200) are obtained.

[0105] Method for manufacturing a reflective mask

[0106] FIG. 5 is a manufacturing process diagram illustrating a method for manufacturing a reflective mask according to the present invention, and is a diagram showing the steps for manufacturing a reflective mask (200) illustrated in FIG. 2 using a mask blank (100) illustrated in FIG. 1. Hereinafter, a method for manufacturing a reflective mask will be described based on FIG. 5.

[0107] First, as shown in FIG. 5(a), a mask blank (100) is prepared. This mask blank (100) is the mask blank (100) described using FIG. 1, and, for example, an etching mask film (5) is formed on a thin film (4). However, if the mask blank (100) does not have an etching mask film (5), an etching mask film (5) is formed on the thin film (4). After that, a resist film (20) is formed on the etching mask film (5), for example by spin coating. In addition, the mask blank (100) may also have a resist film (20), in which case the step of forming the resist film (20) is unnecessary.

[0108] Next, as shown in FIG. 5(b), a resist pattern (20a) is formed by patterning the resist film (20) by performing a lithography treatment on the resist film (20). In this lithography treatment, for example, exposure by electron beam lithography, development treatment, and rinsing treatment are performed.

[0109] Next, as shown in FIG. 5(c), the etching mask film (5) is etched using the resist pattern (20a) as a mask to form the etching mask pattern (5a). After that, the resist pattern (20a) is removed using an ashing agent or a resist stripping agent.

[0110] Next, as shown in FIG. 5 (d), the etching mask pattern (5a) is used as a mask, and the thin film (4) is etched to form a transfer pattern (4a). At this time, the thin film (4) is a TaMoN thin film with a nitrogen content [N] / [Ta+Mo] of 0.15 or higher. Accordingly, dry etching is performed using chlorine gas (Cl2) as the etching gas. In this etching, a protective film (3) made of a material containing ruthenium (Ru) or silicon oxide (SiO2) acts as an etching stopper, and etching damage is prevented from being applied to the multilayer reflective film (2).

[0111] After the above, the reflective mask (200) shown in FIG. 2 is obtained by removing the etching mask pattern (5a). Additionally, wet cleaning using an acidic or alkaline aqueous solution is performed to remove the etching mask pattern (5a). Even during this wet cleaning, damage to the multilayer reflective film (2) is prevented by the protective film (3).

[0112] In the above method for manufacturing a reflective mask (200), since a transfer pattern (4a) is formed by etching a thin film (4) with a high etching rate, productivity can be improved. In addition, the thin film (4) is patterned by etching in which the etching selectivity ratio for the etching mask pattern (5a) and the protective film (3) is maintained at a high level. Because of this, the shape precision and miniaturization can be improved by thinning the etching mask pattern (5a). It is also possible to prevent surface roughness of the protective film (3).

[0113] Method for manufacturing a semiconductor device

[0114] The method for manufacturing a semiconductor device according to the present invention is characterized by using the reflective mask (200) described above and exposing and transferring the transfer pattern (4a) of the reflective mask (200) onto a resist film on a substrate. The method for manufacturing such a semiconductor device is performed as follows.

[0115] First, a substrate for forming a semiconductor device is prepared. This substrate may be, for example, a semiconductor substrate, a substrate having a semiconductor thin film, or a substrate on which a microprocessing film is formed. A resist film is formed on the prepared substrate, and a pattern exposure is performed on the resist film using the reflective mask (200) of the present invention, and a transfer pattern (4a) formed on the reflective mask (200) is exposed and transferred to the resist film. At this time, EUV light is used as the exposure light.

[0116] After the above, the resist film on which the transfer pattern (4a) has been exposed and transferred is developed to form a resist pattern, and using this resist pattern as a mask, etching is performed on the surface layer of the substrate, or impurities are introduced. After the processing is finished, the resist pattern is removed.

[0117] By performing the above processing and further necessary processing, the semiconductor device is completed.

[0118] In the manufacture of a semiconductor device as described above, by using a reflective mask (200) having a transfer pattern (4a) with good shape precision and performing pattern exposure with EUV light as the exposure light, a resist pattern with sufficient precision to satisfy the initial design specifications can be formed on a substrate. Furthermore, if the reflective mask (200) is a reflective phase shift mask, the occurrence of a shadowing effect is suppressed, thereby allowing a resist pattern with good shape precision and positional precision to be formed. In the above respects, when a circuit pattern is formed by dry etching a lower layer film using the pattern of the resist film as a mask, a high-precision circuit pattern can be formed without wiring short circuits or open circuits caused by insufficient precision.

[0119] Examples

[0120] Next, an embodiment applying the present invention will be described. FIG. 6 is a diagram showing the thin film composition and physical properties of the thin film of the embodiment. Hereinafter, Examples No. 1-13 will be described with reference to FIG. 1 and FIG. 6 above.

[0121] <Examples No. 1-12>

[0122] The mask blank (100) of Example No. 1-12 was prepared as follows. First, a SiO2-TiO2 glass substrate, which is a low thermal expansion glass substrate of size 6025 (approx. 152 mm × 152 mm × 6.35 mm) with main surfaces on both sides polished, was prepared and used as the substrate (1). Polishing was performed, consisting of a rough polishing process, a precision polishing process, a local processing process, and a touch polishing process, so that the main surfaces on both sides of the substrate (1) would be flat and smooth.

[0123] Next, the main surface of one side of the substrate (1) was made into a back side (1b), and a conductive film (10) made of a CrN film was formed on the back side (1b) by magnetron sputtering (reactive sputtering). The conductive film (10) was formed using a Cr target in a mixed gas atmosphere of argon (Ar) gas and nitrogen (N2) gas to have a film thickness of 20 nm.

[0124] Next, the side opposite to the back side (1b) where the conductive film (10) is formed is designated as the main surface (1a) of the substrate (1), and a multilayer reflective film (2) is formed on this main surface (1a). In order to make the multilayer reflective film (2) formed on the substrate (1) suitable for EUV light with a wavelength of 13.5 nm, it is made into a periodic multilayer reflective film composed of molybdenum (Mo) and silicon (Si). The multilayer reflective film (2) is formed by using a Mo target and a Si target, and by alternately stacking Mo layers and Si layers on the substrate (1) by an ion beam sputtering method in a krypton (Kr) gas atmosphere. First, a Si film is formed with a film thickness of 4.2 nm, and subsequently, a Mo film is formed with a film thickness of 2.8 nm. This was set as one cycle, and 40 cycles were stacked in the same way, and finally, a Si film was formed with a film thickness of 4.0 nm to form a multilayer reflective film (2).

[0125] Next, in an Ar gas atmosphere, a protective film (3) made of RuRh film was formed on the surface of a multilayer reflective film (2) by RF sputtering using a RuRh target (Ru:Rh=8:2 atomic % ratio) to a film thickness of 2.6 nm.

[0126] Next, a TaMoN film was formed as a thin film (4). At this time, in a PVD (Physical Vapor Deposition) apparatus using a tantalum (Ta) target and a molybdenum (Mo) target, the thin film (4) was formed to have a film thickness of 50 nm by reactive sputtering (co-sputtering) using nitrogen gas (N2) as the sputtering gas. In addition, in the formation of each thin film (4) of Examples No. 1-12, the ratio of tantalum (Ta) and molybdenum (Mo) in the target, the flow rate of nitrogen gas (N2), and the gas pressure were adjusted to obtain the thin films (4) of each composition shown in FIG. 6. In addition, the composition of each thin film (4) is a value obtained by elemental analysis by RBS (Rutherford Backscattering Spectrometry).

[0127] <Example No. 13>

[0128] Example No. 13 is different from the manufacturing procedure of the mask blank (100) of Examples No. 1-12 in that a thin film of tantalum (Ta)-molybdenum (Mo) alloy is deposited as the thin film (4). At this time, a thin film of tantalum (Ta)-molybdenum (Mo) alloy with a thickness of 50 nm was deposited by co-sputtering using a tantalum (Ta) target and a molybdenum (Mo) target in an argon gas atmosphere. The composition of the thin film of tantalum (Ta)-molybdenum (Mo) alloy is a value obtained by elemental analysis by RBS.

[0129] ≪Evaluation of Thin Films in Each Mask Blank≫

[0130] The thin films of the mask blanks prepared in Examples No. 1-13 were directly deposited onto a substrate, and the physical properties of each deposited thin film were evaluated. The substrate used was the same as the substrate used to prepare the mask blanks.

[0131] Etching Rate

[0132] For each thin film of Examples No. 1-13, the etching rate of each thin film was measured. The etching rate was measured as the etching speed of the thin film (4) when the thin film (4) was exposed to a chlorine gas (Cl2) atmosphere used as an etchant for the thin film (4) when a reflective mask is prepared by processing a mask blank. The result is the etching rate ratio when the etching rate of the tantalum (Ta)-molybdenum (Mo) alloy thin film of Example No. 13 is set to 1, as shown in FIG. 3.

[0133] As explained above using Fig. 3, the TaMoN thin film of Example No. 3-12 (see Fig. 6), which has a nitrogen content ratio [N] / [Ta+Mo] of 0.15 or higher, has an etching rate ratio of 1.5 or higher in dry etching using chlorine gas (Cl2) as an etching gas, which is 1.5 times or higher than the etching rate of the TaMo alloy.

[0134] <Refractive Index and Decay Coefficient>

[0135] For each thin film of Examples No. 1-12, the refractive index [n] and the decay coefficient [k] were calculated. In addition, as a reference example, a TaBN film (a thin film with an atomic ratio of Ta:B:N = 70:15:15 (i.e., a thin film with [Mo] / [Ta+Mo]=0)) was formed on a substrate by sputtering, and the refractive index [n] and the decay coefficient [k] were calculated. The results are shown in Fig. 4 as the relationship between the molybdenum content ratio [Mo] / [Ta+Mo], the refractive index, and the decay coefficient for each thin film of Examples No. 1-12 and the reference example.

[0136] As shown in FIG. 4, it can be seen that the TaMoN film of Examples No. 1-12 (see FIG. 6), in which the molybdenum content ratio [Mo] / [Ta+Mo] is 0.5 or less, maintains a decay coefficient [k] of 0.02 or more with respect to the wavelength of EUV light. In addition, the TaMoN film of Examples No. 1-12, other than the TaBN film of the reference example (a thin film with [Mo] / [Ta+Mo]=0), maintains a refractive index [n] of 0.955 or less with respect to the wavelength of EUV light. Such a TaMoN thin film can set the film thickness to a thinner range, and when the reflective mask (200) is a phase shift mask, the transfer pattern (4a), which is a phase shift pattern, can be thinned, thereby suppressing the occurrence of a shadowing effect of the reflective mask (200).

[0137] Surface roughness

[0138] Surface roughness was measured for each thin film of Examples No. 1-13, and the results are shown together in Fig. 6. Surface roughness [Sq] (root mean square roughness) is a value measured by AFM using a square area with a side length of 1 [㎛] as the measurement area, as previously explained. As shown in Fig. 6, it was confirmed that the surface roughness [Sq] (root mean square roughness) of the TaMoN thin films of Examples No. 3-12, in which the nitrogen content ratio [N] / [Ta+Mo] ≥ 0.15, was suppressed to less than 0.3 [nm].

[0139] Crystallinity

[0140] Crystallinity was evaluated by X-ray diffraction (XRD) for each thin film of Examples No. 1-13, and the results are shown together in Fig. 6. As shown in Fig. 6, the TaMoN thin films of Examples No. 3-12, with a nitrogen content ratio [N] / [Ta+Mo] ≥ 0.15, were confirmed to be amorphous.

[0141] Membrane stress

[0142] Film stress was measured for each thin film of Examples No. 1-13, and the results are shown together in Fig. 6. Film stress was expressed as the difference between the maximum height and the minimum height (substrate bending amount) in the inner region of a rectangle with a side length of 142 mm, centered on the center of the substrate, by calculating the difference between the surface shape of the thin film and the surface shape of the substrate before forming the thin film. In addition, the surface shape of each was measured using the UltraFLAT 200M surface shape measuring device (manufactured by Corning TROPEL).

[0143] As shown in Fig. 6, it was confirmed that the TaMoN thin film of Example No. 3-12, with a nitrogen content ratio [N] / [Ta+Mo]≥0.15, has a film stress (substrate bending amount) of 150 [nm] or less.

[0144] <SPM 막 감소 속도>

[0145] The SPM film reduction rate of each thin film of Examples No. 1-3, 7-11, and 13 was measured for two cleaning cycles as cleaning resistance, and the results are shown together in Figure 6. In this case, the amount of film reduction (SPM film reduction amount) of the thin film after cleaning was measured by exposing the thin film to an SPM (sulfuric acid-hydrogen peroxide mixture cleaning) solution for a predetermined time, and the SPM film reduction rate for each of the two cleaning cycles was calculated.

[0146] As shown in Fig. 6, the SPM film reduction rate of the TaMoN thin film of Example No. 3-12, with a nitrogen content ratio [N] / [Ta+Mo] ≥ 0.15, was slower than the SPM film reduction rate of the TaMo alloy thin film of Example No. 13 during the first cleaning cycle, in both the first and second cleaning cycles. This confirms that the TaMoN thin film with a nitrogen content ratio [N] / [Ta+Mo] ≥ 0.15 has sufficient SPM resistance.

[0147] Contrast

[0148] For each thin film of Examples No. 2, 7-11, and 13, the contrast with ultraviolet light of wavelength 193 nm and visible light of wavelength 405 nm was evaluated. Here, the contrast between each thin film and a multilayer reflective film (2) equipped with a protective film (3) was measured. As a result, it was confirmed that the contrast of the TaMoN thin film of Examples No. 7-11, which has a nitrogen content ratio [N] / [Ta+Mo]≥0.15, is higher than the contrast of the TaMo alloy thin film of Example No. 13, and that accurate inspection using ultraviolet light and visible light as inspection light is possible. Explanation of the symbols

[0149] 1: Substrate 1a: Major surface 2: Multilayer reflective film 3: Shield 4: Thin film 4a: Warrior Pattern 100: Mask Blank 200: Reflective mask

Claims

Claim 1 A mask blank having a multilayer reflective film and a pattern-forming thin film in this order on the main surface of a substrate, wherein the thin film comprises tantalum, molybdenum, and nitrogen, the ratio of the nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum of the thin film is 0.15 or more, and the total content of tantalum, molybdenum, and nitrogen in the thin film is 90 atomic % or more. Claim 2 A mask blank according to claim 1, wherein the ratio of nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 1.0 or less. Claim 3 A mask blank according to claim 1 or 2, wherein the ratio of the molybdenum content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 0.5 or less. Claim 4 delete Claim 5 A mask blank according to claim 1 or 2, wherein the refractive index n of the thin film at the wavelength of extreme ultraviolet light is 0.955 or less. Claim 6 A mask blank according to claim 1 or 2, wherein the decay coefficient k of the thin film at the wavelength of extreme ultraviolet light is 0.02 or greater. Claim 7 A reflective mask comprising, in this order, a multilayer reflective film and a thin film having a transfer pattern formed thereon on the main surface of a substrate, wherein the thin film comprises tantalum, molybdenum, and nitrogen, the ratio of the nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum of the thin film is 0.15 or more, and the total content of tantalum, molybdenum, and nitrogen in the thin film is 90 atomic % or more. Claim 8 A reflective mask according to claim 7, wherein the ratio of nitrogen content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 1.0 or less. Claim 9 A reflective mask according to claim 7 or 8, wherein the ratio of the molybdenum content [atomic %] to the total content [atomic %] of tantalum and molybdenum in the thin film is 0.5 or less. Claim 10 delete Claim 11 A reflective mask according to claim 7 or 8, wherein the refractive index n of the thin film at the wavelength of extreme ultraviolet light is 0.955 or less. Claim 12 A reflective mask according to claim 7 or 8, wherein the decay coefficient k of the thin film at the extreme ultraviolet wavelength is 0.02 or greater. Claim 13 A method for manufacturing a semiconductor device comprising using a reflective mask described in claim 7 or 8 and a process of photolithographically transferring a transfer pattern onto a resist film on a semiconductor substrate.

Citation Information

Patent Citations

  • Mask for extreme ultraviolet ray exposure, mask blank, and exposure method

    JP2006228766A

  • Method of producing substrate, method of producing multi-layer reflection coating-provided substrate, method of producing mask blank, method of producing mask for transfer and substrate processing apparatus

    JP2015028626A

  • Method for manufacturing a mask blank, a transfer mask, and a method for manufacturing a semiconductor device

    KR1020190137790A

  • Half-tone phase inversion blank mask, photomask and manufacturing method thereof

    KR1020140020530A

  • Method for manufacturing reflective mask blanks, reflective masks, and semiconductor devices

    KR1020190117755A